A (Re)investigation of Middle Kingdom Speech Captions in Wrestling Scenes. Issue 1 (June 2017) - Motte, Aurore
This article studies the Reden und Rufe present in Middle Kingdom wrestling scenes found in the tombs of Senbi (Meir), Neheri I (Deir el-Bersha), and Khety (Beni Hassan). Based on a systematic study, some improvements are suggested to previous translations. After offering commentaries and translation(s) for each speech, the relationship between these scenes and those in Old and New Kingdom tombs is considered, and distinctive features highlighted.